The mobile SAR signal N-hydroxypipecolic acid induces NPR1-dependent transcriptional reprogramming and immune priming. Issue 3 (19th April 2021) - Yildiz, Ipek; Mantz, Melissa; Hartmann, Michael; Zeier, Tatyana; Kessel, Jana; Thurow, Corinna; Gatz, Christiane; Petzsch, Patrick; Köhrer, Karl; Zeier, Jürgen
Abstract: N-hydroxypipecolic acid (NHP) accumulates in the plant foliage in response to a localized microbial attack and induces systemic acquired resistance (SAR) in distant leaf tissue. Previous studies indicated that pathogen inoculation of Arabidopsis ( Arabidopsis thaliana ) systemically activates SAR-related transcriptional reprogramming and a primed immune status in strict dependence of FLAVIN-DEPENDENT MONOOXYGENASE 1 (FMO1), which mediates the endogenous biosynthesis of NHP. Here, we show that elevations of NHP by exogenous treatment are sufficient to induce a SAR-reminiscent transcriptional response that mobilizes key components of immune surveillance and signal transduction. Exogenous NHP primes Arabidopsis wild-type and NHP-deficient fmo1 plants for a boosted induction of pathogen-triggered defenses, such as the biosynthesis of the stress hormone salicylic acid (SA), accumulation of the phytoalexin camalexin and branched-chain amino acids, as well as expression of defense-related genes. NHP also sensitizes the foliage systemically for enhanced SA-inducible gene expression. NHP-triggered SAR, transcriptional reprogramming, and defense priming are fortified by SA accumulation, and require the function of the transcriptional coregulator NON-EXPRESSOR OF PR GENES1 (NPR1). Our results suggest that NPR1 transduces NHP-activated immune signaling modes with predominantly SA-dependent and minor SA-independent features. They further support the notion that NHP functions as a mobile immune regulator capable of moving independently of active SA signaling between leaves to systemically activate immune responses. Abstract : N-hydroxypipecolic acid functions as a mobile activator of systemic acquired resistance, induces NPR1-dependent transcriptional reprogramming, and primes plants for enhanced immune responses.